A Systematic Theory of Argumentation: The pragma-dialectical approach - Eemeren, Frans H. van; Grootendorst, Rob (Cambridge University Press, 2003)
In this book two of the leading figures in argumentation theory present a view of argumentation as a means of resolving differences of opinion by testing the acceptability of the disputed positions. Their model of a 'critical discussion' serves as a theoretical tool for analysing, evaluating and producing argumentative discourse. They develop a method for the reconstruction of argumentative discourse that takes into account all aspects that are relevant to a critical assessment. They also propose a practical code of behaviour for discussants who want to resolve their differences in a reasonable way. This is a major contribution to the study of argumentation and will be of particular value to professionals and graduate students in speech communication, informal logic, rhetoric, critical thinking, linguistics, and philosophy.